Community antibiotic prescribing for children in France from 2015 to 2017: a cross-sectional national study. (25th May 2020) - Trinh, Nhung T H; Cohen, Robert; Lemaitre, Magali; Chahwakilian, Pierre; Coulthard, Gregory; Bruckner, Tim A; Milic, Dejan; Levy, Corinne; Chalumeau, Martin; Cohen, Jérémie F
Abstract: Objectives: To assess recent community antibiotic prescribing for French children and identify areas of potential improvement. Methods: We analysed 221 768 paediatric (<15 years) visits in a national sample of 680 French GPs and 70 community paediatricians (IQVIA's EPPM database), from March 2015 to February 2017, excluding well-child visits. We calculated antibiotic prescription rates per 100 visits, separately for GPs and paediatricians. For respiratory tract infections (RTIs), we described broad-spectrum antibiotic use and duration of treatment. We used Poisson regression to identify factors associated with antibiotic prescribing. Results: GPs prescribed more antibiotics than paediatricians [prescription rate 26.1 (95% CI 25.9–26.3) versus 21.6 (95% CI 21.0–22.2) per 100 visits, respectively; P <  0.0001]. RTIs accounted for more than 80% of antibiotic prescriptions, with presumed viral RTIs being responsible for 40.8% and 23.6% of all antibiotic prescriptions by GPs and paediatricians, respectively. For RTIs, antibiotic prescription rates per 100 visits were: otitis, 68.1 and 79.8; pharyngitis, 67.3 and 53.3; sinusitis, 67.9 and 77.3; pneumonia, 80.0 and 99.2; bronchitis, 65.2 and 47.3; common cold, 21.7 and 11.6; bronchiolitis 31.6 and 20.1; and other presumed viral RTIs, 24.1 and 11.0, for GPs and paediatricians, respectively. For RTIs, GPs prescribed more broad-spectrum antibiotics [49.8% (95% CI 49.3–50.3) versus 35.6% (95% CI 34.1–37.1), P <  0.0001] and antibiotic courses of similar duration ( P =  0.21). After adjustment for diagnosis, antibiotic prescription rates were not associated with season and patient age, but were significantly higher among GPs aged ≥50 years. Conclusions: Future antibiotic stewardship campaigns should target presumed viral RTIs, broad-spectrum antibiotic use and GPs aged ≥50 years.